The prognostic significance of lymphovascular tumor invasion in localized high‐grade osteosarcoma: Outcomes of a single institution over 10 years. Issue 7 (23rd February 2021) - Gusho, Charles A.; Miller, Ira; Clayton, Bishir; Colman, Matthew W.; Gitelis, Steven; Blank, Alan T.
Abstract: Backgrounds and Objectives: Lymphovascular invasion (LVI) has shown evidence of an association with worse survival in high‐grade osteosarcoma patients. The purpose of this investigation was to prognosticate LVI as a predictor of survival. Methods: This was a retrospective review of high‐grade, localized osteosarcoma patients over a consecutive 10‐year period. Proportional hazards regression was used to identify prognostic factors. Cumulative mortality incidence was estimated with recurrence as a competing risk. Results: Forty‐two cases with a median follow‐up of 64 months (range, 6–158 months) were reviewed. LVI was present in 21.4% ( n = 9) cases. The five‐ and ten‐year survivals in LVI (+) were 40% and 20%, compared to 93% and 81% in LVI (−), respectively ( p < .001). After controlling for confounders, advanced age (hazards ratio [HR], 1.134; 95% confidence interval [CI], 1–1.2; p = .01) and LVI (HR, 21.768; 95% CI, 3–135; p = .001) were negative prognosticators. The cumulative incidence of recurrence was no different between LVI (+) and LVI (−) ( p = .811), though the incidence of mortality was significantly higher in LVI (+) ( p = .003). Conclusion: The presence of LVI in the setting of high‐grade, localized osteosarcoma is associated with greater rates of mortality and appears to portend a dismal prognosis.